Validation and reliability of the Care Vulnerability Index: A study by interrater agreement and test–retest method - Marta Fernández Batalla; Enrique Monsalvo San Macario; Alexandra González Aguña; Sara Herrero Jaén; Blanca Gonzalo de Diego; Yolima Manrique Anaya; M. Lourdes Jiménez Rodríguez; Estela Melguizo Herrera; José María Santamaría García (Nursing Open, 2022)
Abstract Aim The aim of this study is to determine the validity and reliability of the Care Vulnerability Index (CVI) as a tool to estimate the need and competence of care. Design A cross‐sectional survey including a longitudinal component. Methods Content validity ratio (CVR) was calculated by interrater agreement of a group of 11 experts in two rounds. The test–retest analysis was measured in an urban population of Colombia with 96 participants through two statistical tests: Pearson's correlation coefficient and the difference in means. Results Care Vulnerability Index turned out to be valid with a CVR of 0.879. Reliability by Pearson correlation between test–retest was 0.912 (CI95: 0.872–0.941; p‐value <.01) and there was no significant mean difference between test and retest in global score and in clustered groups of variables. Validating CVI will make it possible to prioritize healthcare resources in the population and identify people susceptible to care problems.